2014
DOI: 10.1124/jpet.114.216804
|View full text |Cite
|
Sign up to set email alerts
|

M1and M2Muscarinic Receptor Subtypes Regulate Antidepressant-Like Effects of the Rapidly Acting Antidepressant Scopolamine

Abstract: Scopolamine produces rapid and significant symptom improvement in patients with depression, and most notably in patients who do not respond to current antidepressant treatments. Scopolamine is a nonselective muscarinic acetylcholine receptor antagonist, and it is not known which one or more of the five receptor subtypes in the muscarinic family are mediating these therapeutic effects. We used the mouse forcedswim test, an antidepressant detecting assay, in wild-type and transgenic mice in which each muscarinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…These results have important clinical implications, especially in light of the evidence demonstrating rapid antidepressant effects following systemic administration of the mAChR antagonist, scopolamine [10, 24, 40]. Based on our findings, we suggest that additional VTA mAChR examination may provide important, new understanding of the neurobiological mechanisms that underlie stress and anxiety-related disorders.…”
Section: Discussionsupporting
confidence: 63%
“…These results have important clinical implications, especially in light of the evidence demonstrating rapid antidepressant effects following systemic administration of the mAChR antagonist, scopolamine [10, 24, 40]. Based on our findings, we suggest that additional VTA mAChR examination may provide important, new understanding of the neurobiological mechanisms that underlie stress and anxiety-related disorders.…”
Section: Discussionsupporting
confidence: 63%
“…These antidepressant effects in animal models were shown to be mediated by the effects of scopolamine to block the M1 subtype of mAChRs [81, 85], however, some evidence for M2 mAChR blockade as the mediator of these effects of scopolamine in animal models also exists [86]. …”
Section: Scopolamine As a Rapid-acting Antidepressantmentioning
confidence: 99%
“…Furthermore, repeated administration of scopolamine and VU0255035 reduced anhedonia in CUS-exposed rats [91]. A separate study using higher doses of scopolamine indicated that mutant mice lacking M1- or M2-ACh receptor do not show antidepressant responses to scopolamine [92]. In this context it is relevant to note that prior studies with other partially selective M1-AChR compounds (i.e., biperiden) report antidepressant effects in severely depressed, but not moderately depressed patients [89, 93].…”
Section: Scopolaminementioning
confidence: 99%